The effect of leg ischemia/reperfusion injury on the liver in an experimental breast cancer model - Erkent, Murathan; Dinç Akbulut, Güneş; Horzum, Utku; Aydın Meriçöz, Çisel; Esendağlı, Güneş (Journal of Surgery and Medicine, 2021)
Background/Aim: Ischemia/reperfusion (I/R) injury occurs during breast cancer surgery, especially those involving a modified radical mastectomy, lumpectomy, and axillary lymph node dissection. Tissue damage and stress due to I/R alter immune system functions, especially those of the myeloid cells. The immunologic impact of this I/R injury on myeloid-derived cancerous cells remains unknown. We sought to investigate the effect of I/R injury in the extremity close the breast tumor location on myeloid cell population in the liver and liver metastasis. Methods: 4T1 breast tumors were created in the left inguinal breast region of the experimental animals. When the tumor reached 0.5 cm in diameter, ischemia was produced on the left down-extremity for 90 min and reperfusion was induced for short (3 days), middle (7 days), and long terms (14 days). At the end of the reperfusion period, proximal limbs and livers were harvested. The limb and liver samples were histopathologically examined with H&E staining. Immune cell percentages were determined in the liver by flow cytometry. Results: There was an increase in muscle fiber degeneration and disorganization in the I/R induced proximal legs on days 3 and 7 of I/R in both tumor free and tumor bearing animals with a further impact in tumor bearing mice. Even though I/R injury did not affect tumor metastasis to the liver, it had an impact on liver myeloid cell percentages in both tumor free and tumor bearing animals. Additionally, tumor bearing mice demonstrated higher myeloid cell percentages in both the pre-I/R and post-I/R experimental groups. There was a remarkable change in the levels of granulocytic, and monocytic myeloid cells and macrophages due to the I/R injury. Conclusion: With the formation of short-term I/R injury in a distant site, tumor development and/or seeding to metastasis sites after surgery could be prevented. This study contributes to the understanding of the inflammatory process after I/R injury occurring during interventions.